Comparison of aggregates properties from "West Java and Banten Province" and "Northern Ireland" - Djoko Widajat (Jurnal Jalan-Jembatan, 2009)
Many types of aggregates are found in West Java and Banten Province and Northern Ireland where they are regarded as a valuable resource that is used to construct highways. There is a distinct difference in the specific types of aggregates present in each countries i.e. andesite in West Java and Banten Province and olivine basalt in Northern Ireland. Correlation of physical and mechanical data indicates that Northern Ireland aggregates are typically denser and stronger than the West Java and Banten aggregates.